2010
DOI: 10.1016/j.ces.2010.03.056
|View full text |Cite
|
Sign up to set email alerts
|

The role of kinetics in the design of plasma microreactors

Abstract: Miniaturisation of plasma reactors has the potential of low power operation. In general, the electric field strength in the gap between two electrodes increases proportionate to inverse of the gap width, so that it is possible to Overcome the first ionization potential of the gas with a low voltage. However, plasmas are extinguished primarily by recombination at the walls. Wall collisions are enhanced by the greater surface area to volume ratio in microchannels, which also increases proportionate to the invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 6 publications
(4 reference statements)
1
28
0
Order By: Relevance
“…Much more reactive chemical species other than hydroxyl radical can be produced, such as hydrogen peroxide, hydroperoxyl and ozone. Zimmerman et al devoted to the investigation of the ozone formation reaction in a microchannel plasma reactor [27,28]. Furthermore, shock waves and UV light formed by discharge also can be favorable during water treatment [29].…”
Section: Introductionmentioning
confidence: 99%
“…Much more reactive chemical species other than hydroxyl radical can be produced, such as hydrogen peroxide, hydroperoxyl and ozone. Zimmerman et al devoted to the investigation of the ozone formation reaction in a microchannel plasma reactor [27,28]. Furthermore, shock waves and UV light formed by discharge also can be favorable during water treatment [29].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen economy could offer advantages both in terms of lower green house gasses (GHGs) emissions and as an alternative fuel which would eventually reduce the consumption rate of fossil fuels. Hydrogen fuel produced by a renewable energy source such as wind or solar would be totally green and renewable [1,2]. For the development of the hydrogen economy it is very important to have hydrogen production processes which could produce hydrogen efficiently, at a cost comparable to that of fossil fuel and should be environment friendly [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that in order to keep the optimal level of electrical field constant, the external applied voltage must be decreased as the dimensions of the system are reduced. The low voltage applied is a key factor for an effective reduction of plasma temperature [17]. These conditions contribute to cutting down the operating cost since the ozone generation is more effective at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Advantages of the DBD plasma reactor downscaling has been numerically proven with an application of COMSOL Multiphysics software [15,17]. It was shown that in order to keep the optimal level of electrical field constant, the external applied voltage must be decreased as the dimensions of the system are reduced.…”
Section: Resultsmentioning
confidence: 99%